ChemInform Abstract: Reaction of gem‐Difluorinated Organozinc Reagents with β‐Nitrostyrenes. Issue 47 (November 2015) - Kondratyev, Nikolay S.; Levin, Vitalij V.; Zemtsov, Artem A.; Struchkova, Marina I.; Dilman, Alexander D.
Abstract: A novel reactivity pattern of gem‐difluorinated organozinc compounds in the copper(I)‐catalyzed reaction with β‐nitrostyrenes is described.